24-h movement behaviors among autistic adults: Differences by sex, age, and level of independence. Issue 4 (October 2021) - Healy, Sean; Brewer, Benjamin; Palmiere, Katherine; Daly, Julie; McGuire, Joseph; Patterson, Freda
Abstract: Background: Autistic adults have low levels of physical activity [PA], high levels of sedentary behavior [SB], and insufficient sleep. Not known is the extent to which engagement in these movement behaviors vary by sex, age, and level of independence in activities of daily living (ADLs). Objective: To characterize movement behaviors in a national sample of autistic adults by sex, age, and level of independence in ADLs. Methods: A national sample of autistic adults and caregivers of autistic adults self-reported PA, SB and sleep behaviors as well as demographic variables using an electronic survey. Levels of engagement in movement behaviors were described, and compared by sex, age (young-adult versus middle-age), and level of independence in ADLs. Results: Data were collected on 361 autistic adults (60.3% male, n  = 217, m age  = 30.82 years, SD  = 10.24). Overall, 44% did not meet the PA guideline; PA guideline adherence was lowest among males and those who were dependent on others in ADLs. Overall, the SB guideline was not met by 43% of the sample at weekdays and 48% at weekends. SB guideline adherence was lowest among adults who were middle-aged, and those who were fully independent in ADLs. Overall, 35.2% did not meet the total sleep time (TST) guideline. Middle-aged autistic adults had the lowest adherence to the TST guideline. Conclusions: These finding should prompt researchers to consider these demographic differences, and tailor research and programmatic efforts to account for the unique movement behavior profiles of different segments of this heterogenous population.